Microbiota-supportive diets and hyperlipidemia: The mediating role of systemic inflammation - Wenjing Wang; Weinan Jiang (PLoS ONE, 2025)
Background Hyperlipidemia is a major modifiable risk factor for cardiovascular disease, and emerging evidence suggests a critical role of the gut microbiota in lipid metabolism. The Dietary Index for Gut Microbiota (DI-GM) is a novel tool designed to capture the microbiota-supportive potential of habitual dietary patterns, yet its association with lipid abnormalities remains underexplored in large populations. Methods We analyzed data from 21,352 adults in the 2010–2020 cycles of the National Health and Nutrition Examination Survey (NHANES). The DI-GM, reflecting 14 microbiota-relevant dietary components, was derived from 24-hour recall data. Hyperlipidemia was defined using standard lipid thresholds or lipid-lowering medication use. Survey-weighted logistic regression, restricted cubic spline analysis, and mediation analysis using the systemic immune-inflammation index (SII) were performed to assess associations and potential mechanisms. Results Higher DI-GM scores were significantly associated with lower odds of hyperlipidemia (fully adjusted OR for highest vs. lowest category = 0.806; 95% CI: 0.735–0.883). A dose–response relationship was confirmed in spline models. Mediation analysis showed that systemic inflammation, as quantified by SII, accounted for 17.8% of the observed association, suggesting an immunometabolic pathway linking diet and lipid status. Conclusion Microbiota-oriented dietary patterns, as captured by the DI-GM, are inversely associated with hyperlipidemia in U.S. adults. These findings highlight the value of integrating microbiome-relevant dietary assessment into lipid management strategies. Partial mediation by systemic inflammation underscores a potential mechanistic link warranting further investigation through longitudinal and interventional studies.